Laser Welded versus Resistance Spot Welded Bone Implants: Analysis of the Thermal Increase and Strength - Carlo Fornaini; Marco Meleti; Mauro Bonanini; Giuseppe Lagori; Paolo Vescovi; Elisabetta Merigo; Samir Nammour (The Scientific World Journal)
Introduction. The first aim of this “ex vivo split mouth” study was to compare the thermal elevation during the welding process of titanium bars to titanium implants inserted in pig jaws by a thermal camera and two thermocouples. The second aim was to compare the strength of the joints by a traction test with a dynamometer. Materials and Methods. Six pigs’ jaws were used and three implants were placed on each side of them for a total of 36 fixtures. Twelve bars were connected to the abutments (each bar on three implants) by using, on one side, laser welding and, on the other, resistance spot welding. Temperature variations were recorded by thermocouples and by thermal camera while the strength of the welded joint was analyzed by a traction test. Results. For increasing temperature, means were 36.83 and 37.06, standard deviations 1.234 and 1.187, and P value 0.5763 (not significant). For traction test, means were 195.5 and 159.4, standard deviations 2.00 and 2.254, and P value 0.0001 (very significant). Conclusion. Laser welding was demonstrated to be able to connect titanium implant abutments without the risk of thermal increase into the bone and with good results in terms of mechanical strength.